The intersection of race and femininity in the classroom - Faber, Naomi S.; Williams, Monnica T. (Frontiers in Psychology, 2023)
This vignette told in eight graphic panels illustrates a story about how emotional responses associated with White femininity are used to derail a classroom discussion about racial injustice in a university setting. The panels show how this weaponization of femininity occurs and how it shields those who wield it from external criticism while centering themselves in conversations about race. Women of other races typically cannot access this psychological tactic, thus it constitutes a strategic intersectional use of race, psychology, and privilege to access a power position. In offering suggestions on how to respectfully engage in situations in which racial injustice is a topic of discussion, we unveil how failure of emotional regulation is part of the core psychological framework that leads to these kinds of power dynamics.